2019
DOI: 10.1155/2019/7341841
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of Electronic Health Records for Public Health in Asia: A Review of Success Factors and Potential Challenges

Abstract: Introduction. Electronic health records offer a valuable resource to improve health surveillance and evaluation as well as informing clinical decision making. They have been introduced in many different settings, including low- and middle-income countries, yet little is known of the progress and effectiveness of similar information systems within Asia. This study examines the implementation of EHR systems for use at a population health level in Asia and to identify their current role within public health, key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 45 publications
0
37
0
4
Order By: Relevance
“…In Asia, incapacitated human resources and shortage of IT skills were identified as inhibiting factors to EHIS implementation [49]. In Iran, lack of users' knowledge about system and working with it were the barriers identified [50].…”
Section: Poor Application Of Proven Diffusion Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Asia, incapacitated human resources and shortage of IT skills were identified as inhibiting factors to EHIS implementation [49]. In Iran, lack of users' knowledge about system and working with it were the barriers identified [50].…”
Section: Poor Application Of Proven Diffusion Techniquesmentioning
confidence: 99%
“…Studies revealed incompleteness of TB data across multiple information systems in South Africa. Variances between 12% and 38% of the missed cases due to poor recording from the source documents (either patient records or laboratory records) were demonstrated [49,50]. Data collected and reported in the public health system across three large, high HIV-prevalence districts was neither complete nor accurate enough to guide patient tracking as part of prevention of mother to child transmission (PMTCT) care [51].…”
Section: Compromised Data Qualitymentioning
confidence: 99%
“…It is a technology that can offer considerable healthcare benefits [ 12 , 13 , 56 ] for both developed as well as developing economies [ 57 ]. It can save the cost of healthcare delivery through telemedicine [ 14 , 48 ], enhance access through cloud-based mobile applications [ 15 , 16 ], and improve efficiency and productivity through electronic health records [ 17 , 58 , 59 ].…”
Section: Cloud Adoption In Healthcarementioning
confidence: 99%
“…Adoption of cloud and other digital solutions aims to make healthcare data more accessible to a range of stakeholders, including healthcare workers, caregivers, insurers, and companies that develop new healthcare solutions for the ageing population. It also reduces the increasing burden on healthcare in terms of cost savings, in terms of per capita GDP, and resource optimization [ 14 , 17 , 48 , 54 , 58 , 133 ].…”
Section: Drivers Of Cloud Adoption In Healthcarementioning
confidence: 99%
“…Dornan et al . [ 16 ] showed that many Asian countries have medical records implemented. However, these data collections are not interconnected among the medical institutions, which makes them unusable for Machine Learning analysis.…”
Section: The Basis For Machine Learning In Healthcare: Electronic Heamentioning
confidence: 99%